Registration of commercial and licence agreements in the Common Market - Lewis, A. K.; Kemp, John A. (London : Butterworths, 1962)
This book gives an account of how the treaty and the regulations made under it operate the in case of allegedly restrictive agreement .
osa;29/6/17
Loans
Keywords: License agreements; Exclusive contracts - - European Economic Community countries; Exclusive contracts; Restraint of trade; Exclusive contracts - - European Economic Community countries; License agreements - European Economic Community countries